2019
DOI: 10.1080/00141844.2019.1696855
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguity in a Charismatic Revival: Inverting Gender, Age and Power Relations in Vanuatu

Abstract: During a Christian revival movement on Ahamb Island in Vanuatu in 2014, gender-and agebased hierarchies were inverted as women and children were given divine authority and men were positioned as threats to sociopolitical renewal. In analysing these events, I develop Kapferer's insights on the inherent openness and unpredictability of ritual dynamics.However, I argue that such openness and unpredictability can also be tied to external factors including participants' multiple and sometimes incompatible values an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Akin to Hubert and Mauss (1964), to set the foundations for such ‘society’ one must build and re‐build the original link of mutual belonging. On Ahamb, this is one of commitment to kin and Christian fellowship where everyone subscribes to the same values of love and unity (see Bratrud 2019b).…”
Section: Everyday Relations Of Interdependencementioning
confidence: 99%
“…Akin to Hubert and Mauss (1964), to set the foundations for such ‘society’ one must build and re‐build the original link of mutual belonging. On Ahamb, this is one of commitment to kin and Christian fellowship where everyone subscribes to the same values of love and unity (see Bratrud 2019b).…”
Section: Everyday Relations Of Interdependencementioning
confidence: 99%
“…As a result, visionaries reported that sorcerers from the whole district were flying in to Ahamb in invisible form (suu) to try to kill anyone they could get hold of. 8 These revelations of the intense threat from sorcery came every day for about three months, generating a strong moral and existential panic on the island (see Bratrud 2017;2020). Eventually, however, the strong prayers on the island allegedly led the Holy Spirit to produce a shield of near-complete protection against all 'evil forces' (ol ivil paoa).…”
Section: A Killingmentioning
confidence: 99%
“…Foregrounding the children also demonstrated the Christian emphasis on humility illustrated in Bible texts where Jesus proclaims that the lowly children are the greatest in the kingdom of Heaven (Matthew 18:1‐5; Luke 18:15‐17; Mark 10:14‐16). This was interpreted by revival supporters as criticism of the men who engaged themselves in political disputes at the expense of others’ wellbeing (see Bratrud 2019).…”
Section: Revival and The Hope Of Transgressing Divisionmentioning
confidence: 99%
“…Their role was also connected to the Biblical theorem that one must become humble like a little child to enter the Kingdom of God (see Mark 10:14-16; Luke 18:15-17; Matthew 18:3). For revival supporters, the latter worked as a criticism of the adult men who cultivated their own desires in land claims and political strife, without thinking of others (Bratrud 2019a). As a contrast, the children exemplified the values of humility, obedience and love.…”
Section: The Revival: Recovering Ahamb's Moral Ordermentioning
confidence: 99%